2022
DOI: 10.3390/life12050764
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin, Liraglutide, and Their Combination Attenuate Diabetes Mellitus-Associated Hepato-Renal Injury—Insight into Oxidative Injury/Inflammation/Apoptosis Modulation

Abstract: In this study, we aim to explore the beneficial therapeutic impacts of dapagliflozin (Dapa), a highly potent, reversible, and selective sodium–glucose cotransporter-2 inhibitor, and liraglutide (Lira), a glucagon-like peptide-1 (GLP-1) receptor agonist, as hypoglycaemic agents for the management of diabetes mellitus (DM), as well as their combination against DM-induced complications, including hepato-renal injury. Indeed, the progression of DM was found to be associated with significant hepatic and renal injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recent studies have shown potential for its use in situations where inflammation, oxidative stress, and apoptosis are present. Several authors have shown reduced lipid peroxidation, reduced NFκB, TNF-α, IL-1, IL-6, nitrous oxide production, apoptosis, and cardiac collagen deposition with the use of GLP-1 analogues in some experimental models of disease [ 9 , 10 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In our study, we investigated the role of liraglutide on doxorubicin-induced cardiac toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown potential for its use in situations where inflammation, oxidative stress, and apoptosis are present. Several authors have shown reduced lipid peroxidation, reduced NFκB, TNF-α, IL-1, IL-6, nitrous oxide production, apoptosis, and cardiac collagen deposition with the use of GLP-1 analogues in some experimental models of disease [ 9 , 10 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In our study, we investigated the role of liraglutide on doxorubicin-induced cardiac toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we did not set up a blank control group using the TPU membrane alone, and prospective observation was lacking, which may offset the results. In addition, the safety of TPU/NS dressings should be evaluated by determining the liver and kidney function in diabetic patients with open fractures of lower extremities, as well as serum deposition because hepatocellular damage and nephropathy were associated with diabetes ( 32 ). Furthermore, the wound-healing rate would be assessed in the future to validate our clinical results.…”
Section: Discussionmentioning
confidence: 99%